Rast and Eucast in Blood Test- A Review - Nirubama.K1, M. P.Brundha2 , Ezhilarasan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
An allergic response is the hypersensitive immune response to a substance which is normally harmless orwould not cause an immune response in everyone. An allergic response can cause several symptoms such asitching, inflammation and tissue injury. The manifestation of allergies is recognized in the form of urticaria,swelling, burning, pain, and dryness of the mucosa, stomatitis. radioallergosorbent test (RAST) which is theradioallergosorbent test used for the confirmation of allergic reaction in the body. This test specifically dealswith the IgE antibodies which are responsible for the allergic reactions on the body. It is very essential to crosscheck the exact history related to allergy. Individual sensitivity and population sensitivity, both are equallyresponsible for skin allergy are the factors which are to be considered. Skin tests become negative underconditions of severe allergic reactions which is determined by graded therapy by freedom from contact andusing epinephrine administration. RAST test is a two-stage procedure. RAST- test is performed accordingto the guidelines of European Committee on Antimicrobial Susceptibility (EUCAST). The reliability ofthe test is high compared to other skin tests. Specificity based on two radioallergosorbent tests is high as90% for inhaled allergens. It shows excellent reproducibility across a full measuring range with the helpof the calibration curve. The RAST test is considered to be extremely sensitive. It shows high specificitywhich binds to allergen-specific IgE. This article mainly deals with the RAST procedure, advantages anddisadvantages of the test.